Application Status of Corrosion and Protection of Coastal Railway OCS Carbon Steel Components - WANG Qing, YANG Jia, QI Fu - gang (Cailiao Baohu)
The current anti - corrosion standards of carbon steel components for OCS (Overhead Catenary System) of electrified railway in China were briefly discussed, and the corrosion situation of OCS steel components of coastal railways was analyzed. Results showed that some of OCS steel components still suffered from severe corrosion after being treated with the traditional hot - dip galvanizing process for corrosion prevention, which indicated that hot - dip galvanized anticorrosive measures were difficult to meet the service life requirements of the coastal railway OCS steel components, and new alternatives must be sought. Based on this, several anti - corrosion systems of catenary steel members were researched and analyzed. Finally, it was believed that for coastal humid, hot and high salt environment, heavy - duty anti - corrosion coatings had good application prospects for the anticorrosion of OCS steel components.